Empowering Local Economy through Enhanced Production and Marketing of Lokan Crackers in Gampong Lamseunia - Ferijal, Teuku; Mustaqimah, Mustaqimah; Moulana, Ryan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This community service program aimed to enhance the production and marketing of Lokan crackers in Gampong Lamseunia through a series of systematically designed activities. Initial SWOT analysis revealed that the production had great potential, though challenges like production consistency and lack of appropriate equipment persisted. Training sessions improved group members' skills in standardizing production processes, from material selection to packaging, and emphasized the importance of branding. Despite some success, achieving uniform cracker cuts remained a challenge, highlighting the need for future innovation in production tools. Packaging and branding training led to an increased understanding of the product's market value, and varied packaging options have since been adopted to attract consumers. Although significant sales growth has yet to be realized, marketing efforts through local kiosks and social media have expanded market reach and consumer awareness. The active participation and enthusiasm of the group members indicate a readiness to develop their business sustainably. Moving forward, the focus will be on optimizing digital marketing strategies and introducing production technologies to address current challenges. This program has laid a strong foundation for economic growth, empowering the local community to fully utilize the potential of Lokan crackers. It is expected that these initiatives will drive sustainable local economic development and improve the welfare of the Gampong Lamseunia community.